GENOME-WIDE ASSOCIATION STUDY OF EXTREME HUMAN LONGEVITY DISCOVERS UNCOMMON LONGEVITY VARIANTS - Gurinovich, Anastasia (Innov Aging, 2019)
The strong heritability of extreme human longevity supports the hypothesis that this is a genetically-regulated trait. However, association studies focused on common genetic variants have discovered a limited number of longevity-associated genes. We conducted a genome-wide association study of 4,216 individuals including 1317 centenarians from the New England Centenarian Study (median age = 104 years) using >9M genetic variants imputed to the HRC panel of ~65,000 haplotypes. The set included approximately 5M uncommon variants. The associations were tested using a mixed effect logistic regression model with genotype-based kinship covariance of the random effects to adjust for cryptic relations using the package GENESIS. The analysis discovered 45 genome-wide significant SNPs (p< 5E-08) including 8 new loci in chromosomes 3, 6, 7, 9, 10, 14 and 15 in addition to the APOE locus. The list includes new pQTLs in serum that suggest a new biological mechanism involved in extreme human longevity.